(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
DLF DLF Limited (Delhi Land Finance) is the largest commercial real estate developer in India. It was founded by Chaudhary Raghvendra Singh in 1946. DLF’s first residential project was Krishna Nagar in East Delhi, which was completed in 1949. Subsequently, the company developed 21 colonies in Delhi. But on the passage of Delhi Development Act in 1957, the company decided to move beyond Delhi and zeroed in on the suburb of Gurgaon in Haryana. DLF is now present across 15 states - 24 cities in India.